2010
DOI: 10.1093/epirev/mxq001
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Nutrition and Birth Outcomes

Abstract: In this review, the authors summarize current knowledge on maternal nutritional requirements during pregnancy, with a focus on the nutrients that have been most commonly investigated in association with birth outcomes. Data sourcing and extraction included searches of the primary resources establishing maternal nutrient requirements during pregnancy (e.g., Dietary Reference Intakes), and searches of Medline for "maternal nutrition"/[specific nutrient of interest] and "birth/pregnancy outcomes," focusing mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
388
0
14

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 503 publications
(432 citation statements)
references
References 120 publications
7
388
0
14
Order By: Relevance
“…This conclusion is in keeping with quantitative genetic reports that BW at full term (44), and associations between BW and later cognitive outcome (44,45), are largely determined by non-genetic sources of variation. The fact that environmental influences on neurocognitive development are not "drowned out" by genetic variation is highly relevant from a public health perspective because (i) there is greater potential to optimize neurodevelopment outcomes through modification of the prenatal environment than by modification of genes; and (ii) it is a favorable (but not sufficient) condition for the success of any potential population-level attempt to modify neurodevelopmental outcomes through environmental interventions targeted at BW optimization (46).…”
Section: Modeling Prenatal Environmental Influences On Brain Developmentmentioning
confidence: 99%
“…This conclusion is in keeping with quantitative genetic reports that BW at full term (44), and associations between BW and later cognitive outcome (44,45), are largely determined by non-genetic sources of variation. The fact that environmental influences on neurocognitive development are not "drowned out" by genetic variation is highly relevant from a public health perspective because (i) there is greater potential to optimize neurodevelopment outcomes through modification of the prenatal environment than by modification of genes; and (ii) it is a favorable (but not sufficient) condition for the success of any potential population-level attempt to modify neurodevelopmental outcomes through environmental interventions targeted at BW optimization (46).…”
Section: Modeling Prenatal Environmental Influences On Brain Developmentmentioning
confidence: 99%
“…Studies have also shown existence of practices and beliefs like denying pregnant and lactating women of known nutritious food items owing to their traditional food habits. [1][2][3] In India most food practices and traditions have stemmed from deeply rooted traditions and customs. These food practices can be attributed to malnutrition, which in turn is linked to poverty, food insecurity, unhygienic practices and traditional beliefs.…”
mentioning
confidence: 99%
“…Maternal nutritional status is a strong predictor of foetal growth and development, with maternal obesity, adiposity, and excessive GWG in particular being associated not only with increased risk of gestational diabetes mellitus (GDM) and pre-eclampsia during pregnancy, but also with adverse birth outcomes such as pre-term birth, still birth, and macrosomia (birth weight > 4 kg) [11,12]. Sub-optimal growth and development, as well as exposure to pregnancy-associated metabolic risk factors, may increase susceptibility to NCDs in later life for both mother and infant [13,14].…”
Section: Maternal Nutrition and Physical Activity During Pregnancymentioning
confidence: 99%